Validation of Indonesian Graves’ Ophthalmopathy Quality of Life Questionnaire and Its Association with Clinical Activity and Severity of Graves’ Ophthalmopathy - CECILIA ANGGRAINI; Syntia Nusanti; Muhammad Sidik; Dicky L Tahapary; Levina Chandra Khoe (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Graves' ophthalmopathy (GO) ocular abnormalities persisted even after treatment, negatively impacting the patient's psychological and social health. The Indonesian Graves' Ophthalmopathy Quality of Life (GO-QoL) Questionnaire has not been validated; hence it cannot measure patient quality of life in Indonesia, which is crucial to GO treatment. This objective of this study is providinga reliable Indonesian GO-QoL questionnaire and identifying an association between patient quality of life and clinical activity and severity of GO. Methods : The cross-sectional study ran from May through October 2022. Graves' ophthalmopathy and thyroid disease management were the inclusion criteria. Those who could not be reached by video call or controlled for two weeks for test-retest data collection were excluded. The process of questionnaire validation involves transcultural adaptation and cross-sectional design. The content validity index (CVI) and Cronbach's alpha assessed validity and reliability, respectively. Results : Content validity index (CVI) was 1.00 for the Indonesian GO-QoL questionnaire. Cronbach's alpha visual function subscale value was 0.971, while the appearance subscale value was 0.993, and the total score was 0.986. The appearance subscale and total score of GO patients' quality of life had a significant association with the clinical activity score (p<0.05) and disease severity (p<0.001). Conclusion : The Indonesian version of the GO-QoL questionnaire has high validity and reliability values. Patients' appearance and overall quality of life decreases with active Graves' ophthalmopathy. Graves' ophthalmopathy severity decreases quality of life on the appearance and overall subscales.